2003
DOI: 10.1021/np020612s
|View full text |Cite
|
Sign up to set email alerts
|

Stemocurtisine, the First Pyrido[1,2-a]azapine Stemona Alkaloid

Abstract: A new pentacyclic stemona alkaloid, stemocurtisine (2), with a novel pyrido[1,2-a]azapine A,B-ring system, has been isolated from a root extract of Stemona curtisii. The structure and relative stereochemistry was determined by spectral data interpretation and X-ray crystallography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 14 publications
2
54
0
Order By: Relevance
“…Results and Discussion (Table 1) were similar to those of 1 [Mungkornasawakul et al, 2003] and indicated the presence of the intact C-and D-ring systems of stemocurtisine. The 13 C NMR spectrum of 2, like that of 1, indicated six quaternary, four methine, six methylene, and three methyl carbons.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…Results and Discussion (Table 1) were similar to those of 1 [Mungkornasawakul et al, 2003] and indicated the presence of the intact C-and D-ring systems of stemocurtisine. The 13 C NMR spectrum of 2, like that of 1, indicated six quaternary, four methine, six methylene, and three methyl carbons.…”
supporting
confidence: 62%
“…To date over 130 different Stemona alkaloids have been isolated with the majority of alkaloids having the pyrrolo[1,2-a]azepine base structure [Pilli et al 2010]. In 2003, we reported the first pyrido[1,2-a]azepine based Stemona alkaloid, stemocurtisine 1 (Scheme 1), which was isolated from the roots of Stemona curtisii found in Trang Province, Thailand [Mungkornasawakul et al, 2003]. Other Stemona alkaloids with a pyrido[1,2-a]azepine structure were later reported by us [Mungkornasawakul et al, 2004;Pyne et al, 2007]], Greger [Kaltenegger et al, 2003] and Ye [Wang et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…The pyrrolo[1,2-a]azepine (5,7-bicyclic A,B-ring system) nucleus is common to all compounds in these groups (e.g., croomine 10). In 2003, we [12] and then Greger [13] reported the structures of Stemona alkaloids with a pyrido[1,2-a]azepine A,B-ring system (that is, a 6,7-bicyclic A,B-ring system), including stemocurtisine 11 and oxystemokerrin 12, and in 2004 we disclosed the structure of another pyrido[1,2-a]azepine Stemona alkaloid, stemocurtisinol 13 [14]. These alkaloids comprise a new and sixth structural group.…”
Section: Stemona Alkaloidsmentioning
confidence: 97%
“…These alkaloids comprise a new and sixth structural group. We [12] and Greger [13] also published the isolation of 14 a new pyrrolo[1,2-a]azepine alkaloid.…”
Section: Stemona Alkaloidsmentioning
confidence: 99%
“…Most of them contain a basic pyrrolo[1,2‐a]azepine core (5,7‐bicycle A,B‐ring system) in their structures. In 2003, stemocurtisine, the first Stemona alkaloid with a pyrido[1,2‐a]azepine A,B‐ring core (6,7‐bicylic A,B‐ring system), was isolated from the roots of S. curtisii Hook 3. Later, some other alkaloids of this type were found, mainly from Stemona species from Vietnam and Thailand 4.…”
mentioning
confidence: 99%